Hak Asasi Manusia dalam Persfektif Islam - Moh. Sholeh (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2018)
As a comparative perspective, human rights originating from the West are legitimized in the Universal Declaration of Human Rights (UDHR) or the Universal Declaration of Human Rights (UDHR) and human rights from an Islamic perspective, as follows: purely philosophical, anthropocentric in nature, more concerned with rights than obligations, more individualistic and human as the full owner of basic rights, while Islamic human rights are. Based on the teachings of the Qur'an and the Sunnah of the Prophet Muhammad SAW, it is Theocentric, the balance between rights and obligations, social interests are prioritized and humans as creatures entrusted with basic rights by God, therefore must be grateful and maintain them. The Qur'an as a source of Islamic law gives high respect to human rights. In the Qur'an there are 80 verses about life, maintenance of life and the provision of means of life. 150 verses about creation and creatures and about equality in creation. There are 320 verses of the Qur'an describing attitudes against injustice and wrongdoers and 50 verses commanding justice. There are 10 verses that talk about the prohibition of coercion to guarantee freedom of thought, belief and expression of aspirations. The Medina Charter consists of 47 articles. The principles of human rights in the Medina Charter are: First, good interaction with others, both Muslims and non-Muslims. Second, help each other in the face of a common enemy. Third, defend those who are persecuted. Fourth, advise each other. And fifth, respecting religious freedom.